Resultados de los experimentos de rendimiento de arroz del IDIAP en 1990 - Batista, E.=700 1 Quiroz, E.; Hernández, R.; De Gutiérrez, G.; Martínez, L.; Him, P.; Vega, F.; Lamboglia, L.C.; Yau, J.; Laáo, R.; Iturralde, E.
Sumario (Es)
Ilus.; 6 ref.
Keywords: ORYZA SATIVA; RENDIMIENTO DE CULTIVOS; VARIEDADES; PANAMA